2019
DOI: 10.1002/ente.201900415
|View full text |Cite
|
Sign up to set email alerts
|

Stepwise Solar Methane Reforming and Water‐Splitting via Lattice Oxygen Transfer in Iron and Cerium Oxides

Abstract: Chemical looping reforming of methane (CLRM) involves lattice oxygen transfer in metal oxides. This study aims to compare iron (Fe 2 O 3) and cerium (CeO 2) oxides as oxygen carrier materials for isothermal solar-driven stepwise CH 4 reforming and H 2 O splitting. Experiments were conducted in a directly-irradiated lab-scale solar reactor heated by concentrated sunlight in the temperature range 950-1150 °C. Using solar energy for process heat reduces the dependence on fossil energy resources and avoids CO 2 em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 40 publications
1
23
0
Order By: Relevance
“…This could come from the reaction of iron oxide with char (2Fe 2 O 3 + 3C → 4Fe+3CO 2 ). The high availability of oxygen from Fe 2 O 3 was also reported in chemical looping methane reforming, leading also to a CO 2 production peak during the first cycle (Chuayboon et al, 2019).…”
Section: Effect Of Oxidizing Agentmentioning
confidence: 61%
“…This could come from the reaction of iron oxide with char (2Fe 2 O 3 + 3C → 4Fe+3CO 2 ). The high availability of oxygen from Fe 2 O 3 was also reported in chemical looping methane reforming, leading also to a CO 2 production peak during the first cycle (Chuayboon et al, 2019).…”
Section: Effect Of Oxidizing Agentmentioning
confidence: 61%
“…They found that the iron yields were extremely low when the reaction temperature was below its melting point due to slow reaction kinetics and diffusion limitation; moreover, the highest iron yields were obtained in a higher temperature range 1850-2390 K, demonstrating a relatively strong effect of the reactor temperature and of the cooling and/or heating rate. The solar Fe 3 O 4 +4CH 4 system was also proposed [121,161] and thermodynamic equilibrium species consisting of solid metallic iron and a gaseous mixture of 2/3 H 2 and 1/3 CO were reported (at 1 bar and 1027 °C), while it was shown experimentally that Fe 3 O 4 reduction with CH 4 depends strongly on both temperature and residence time [71]. The reactivity of magnetite (Fe 3 O 4 ) through CH 4 reforming and H 2 O splitting was investigated in a continuous reactor and the reduction kinetics was also studied [73].…”
Section: Ferritesmentioning
confidence: 97%
“…Compared to the first step in two-step redox cycles, the methane-driven reduction of metal oxides significantly lowers the reduction temperature due to the CH 4 reducing agent [63][64][65][66][67][68][69][70][71].…”
Section: Solar Reforming and Solar Chemical Looping Reforming (Clr)mentioning
confidence: 99%
“…The net products of CLRM are the same as those of steam reforming (Equation 1). The advantages of CLRM through metal oxides over the conventional methane reforming process are (i) the syngas is produced with a H 2 :CO ratio of 2:1 during the first step, suitable for methanol synthesis (Otsuka et al, 1998), (ii) an excess in oxidizer is not necessary, while a conventional process needs to be operated with excess steam (H 2 O:CH 4 ≥ 3) (Simakov et al, 2015), which raises energy requirements and reduces process efficiency, (iii) catalysts are not required, and (iv) an isothermal operation between both steps is possible; therefore, the temperature swing between the reduction and the oxidation steps can be avoided (Chuayboon et al, 2019a), thereby resulting in fast and continuous process operation (no time wasted for cooling down to oxidation temperature) and lower sensible heat losses, thus improving the energy conversion efficiency. Among a variety of potential metal oxides (either volatile or non-volatile), cerium oxide [either pure ceria (Chueh et al, 2010;Furler et al, 2014;Marxer et al, 2017;Haeussler et al, 2019) or ceriabased (Otsuka et al, 1999;Zheng Y. et al, 2014;Zhu et al, 2014;Bhosale et al, 2019)] is a particularly attractive candidate given its various beneficial physical and chemical properties.…”
Section: Introductionmentioning
confidence: 99%